The quality of housing environment and green open space towards quality of life - Ishan, Ainatul Izzah; Mohd Norddin, Nurul Ain; Abdul Malek, Nurhayati; Abu Bakar, Aniza; Othman, Rosniza; Sanusi, Aliyah Nur Zafirah; Mohit, Mohammad Abdul (2014)
The quality of life can be directly influenced by the quality of housing neighbourhood and green open space. Better quality of housing environment and green open space reflects the better quality of life of the residents. Thus, evaluation of both housing environment and green open space can help landscape architects and other related professions to understand people’s needs thus, provide a good living condition and public space to people. This paper is focussing to understand how the residents of Taman Melati perceived their quality of life through their housing environment and the availability of green open space. This research is seeking answers by assessing the quality of life based on three factors which are the safety level of the neighbourhood and park, health issues related to housing environment and park as well as the satisfaction on the housing amenities and park facilities. To carry out the research’s objectives, a case study area was selected at Taman Melati (Mastika), Gombak. The technique used to gather the information needed was by using self-administered questionnaire surveys. 247 questionnaire surveys were distributed to the residents of Taman Melati (Mastika) and (n=62) responded. The expected results of this study are that both elements in the housing neighbourhood and green open space should influence people’s quality of life.